2014
DOI: 10.2134/agronj2013.0345
|View full text |Cite
|
Sign up to set email alerts
|

Soil–Plant Nutrient Interactions on Manure‐Enriched Calcareous Soils

Abstract: Growers working with manured soils o en rely on soil test information when developing nutrient management for their crop, especially when manure application information is unavailable. Nutrient-enriched soils, like manured soils, can trigger nutrient de ciencies and toxicities due to plant-soil nutrient interactions. e goal of the study was to determine correlations between soil test and plant tissue nutrient concentrations for irrigated corn silage crops (Zea mays L. subsp. mays) with varying nutrient concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
3
9
0
3
Order By: Relevance
“…The K content in plants is, in general, negatively correlated with the content of Mg (Ding and Xu 2011). Moore et al (2014) recorded a negative correlation between the K av content in soil and the Mg content in corn tissues.…”
Section: Doi: 1017221/60/2015-psementioning
confidence: 93%
“…The K content in plants is, in general, negatively correlated with the content of Mg (Ding and Xu 2011). Moore et al (2014) recorded a negative correlation between the K av content in soil and the Mg content in corn tissues.…”
Section: Doi: 1017221/60/2015-psementioning
confidence: 93%
“…These effects corroborate those of Hue and Amien (1989), Whalen et al (2000), and Miranda et al (2005), who also reported decreases in these variables (pH index and potential acidity) after application of greater rates of cattle manure and lime. In contrast, the increase in pH and in the availability of soil nutrients can inhibit the rate of uptake of metal micronutrients (Cu, Fe, Mn, and Zn, data not available), as described by Malavolta (2006), Marschner (2012), and Moore et al (2014), causing limitation in the yield and development of the plants. Except for exchangeable K + in the second year of cultivation, the yield of soybean grains showed significant and positive correlations with K + , Ca 2+ , Mg 2+ , CEC, and pH and a negative correlation with exchangeable H + + Al 3+ (Table 2).…”
Section: Grain Yieldmentioning
confidence: 99%
“…Thus, there is a need to find an appropriate soil management strategy that could reduce inorganic fertilization and enhance soil fertility. Nutrient-enriched manure is commonly applied as a cost-effective alternative to inorganic fertilizers (Moore et al, 2014;Leytem et al, 2011). Manure treatment in calcareous soils could be a promising strategy for maintaining soil OM and improve soil physical and biochemical properties (Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%